The righteous revenge of Artemis Bonner - Myers, Walter Dean, 1937- (New York : HarperCollinsPublishers, 1992)
Fifteen-year-old Artemis journeys from New York City to Tombstone, Arizona, in 1882, to avenge the murder of his uncle.
Keywords: Revenge -- Fiction; Buried treasure -- Fiction; African Americans -- Fiction; West (U.S.) -- Fiction